A photographic approach to monitor spatial dynamics and population trends of Arctic Tern colonies in two touristic bird watching spots in the Westfjords, Iceland (Avocetta, 2025)
This study examines the population dynamics and spatial distribution of Arctic Terns in two tourist sites in Iceland's Westfjords: Vigur Island and Súðavík. In 2023, counts revealed 458 terns in Súðavík and 991 in Vigur. We propose a monitoring approach using photography to estimate the population, including non-breeders. Additionally, an interspecies interaction was observed in Vigur, where terns appear to be relocating towards the puffin colony. This behaviour is hypothesised to serve as a defence mechanism against predators, utilising the puffins' frequent, low-altitude flights, as a protective ceiling.